A6.25 Serum concentrations of vascular endothelial growth factor in systemic lupus erythematosus – association with autoantibody profile and cardiovascular involvement. (13th February 2015) - Fischer, K; Przepiera-Będzak, H; Ostanek, L; Walecka, A; Sawicki, M; Brzosko, I; Brzosko, M
Abstract : Background and objectives: Angiogenesis plays a significant role in the pathogenesis of systemic lupus erythematosus (SLE). Vascular endothelial growth factor (VEGF) is a potent stimulator of angiogenesis as well as vasculogenesis. The study was designed to evaluate the association between VEGF concentrations and immunological parameters, inflammatory markers, classical atherosclerosis risk factors and vascular disorders in SLE patients. Materials and methods: The study was performed in 83 patients with SLE and 20 age and gender matched controls. The concentrations of VEGF was determined with ELISA method using R&D Systems tests. The presence of inflammatory markers (ESR, CRP and fibrinogen) and selected autoantibodies - anti-endothelial (AECA), anti-nuclear, anti-phospholipid (aPL) and anti-neutrophil cytoplasmic was evaluated. Classical risk factors for atherosclerosis as well as selected organ manifestations (cardiovascular and central nervous system, lupus nephritis, thromboembolic disorders and vasculitis) were taken into account. Carotid intima-media thickness and atherosclerotic plaques were measured with B-mode ultrasound method. Statistical analysis was performed with chi 2 Yates, chi 2 Pearson, rank Spearman correlations tests, logistic regression analysis and multivariate stepwise analysis. Results: VEGF levels did not differ significantly between SLE patients and the controls (p > 0.1). The cut-off value of VEGF concentrations was established at 382.4 pg/ml (75- percentile). VEGF levels > 382.4 pg/ml were significantly associated with the elongation of activated partial thromboplastin time (OR = 22.8; 95% CI: 2.3–230.6) and the presence of aPL: anti-prothrombin (aPT) IgA class (OR = 10.7; 95% CI: 2.1–53.4), anti- β2-GPI IgA class (OR = 3.5; 95% CI: 1.1–10.8) and anti-oxidised low density lipoprotein antibodies (OR = 4.8; 95% CI: 1.0–22.8). Myocardial relaxation disorders were significantly more frequent in patients with high concentration of VEGF (OR = 8.0; 95% CI: 1.6–39.5). The low concentration of VEGF significantly decreased the risk of the existence of selected autoantibodies: aPT IgA (OR = 0.18; 95% CI: 0.0–0.72), aβ2-GPI IgA (OR = 0.17; 95% CI: 0.04–0.71), anti-double stranded DNA (OR = 0.31; 95% CI: 0, 11–0.91) and AECA (OR = 0.30; 95% CI: 0, 11–0.85). Furthermore, they were associated with reduction of the risk of atherosclerotic lesions in iliac arteries (OR = 0.24; 95% CI: 0.0–0.99) and vasculitis development (OR = 0.17; 95% CI = 0.03–0.91). Conclusions: 1. High VEGF levels may increase the prothrombotic risk in SLE patients because of the significant association with the presence of antiphospholipid antibodies. 2. The lower concentrations of VEGF significantly decrease the risk of persistence of selected autoantibodies and atherosclerotic lesions as well as vasculitis development in SLE patients.